Pengelolaan Arsip Dinamis In-Aktif Menggunakan Aspek Keselamatan, Kesehatan Kerja, dan Lingkungan Hidup di Gedung Sentral Arsip PT Semen Padang - Erlina, Setia Purnama Wia; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper aims to determine the extent of in-active archive management at PT Semen Padang Archival Center by using K3LH aspects which has been accomplished. Data was collected by doing a direct observation and interview. From data related to in-active archive management at PT Semen Padang Archival Center by using K3LH, it can be summarized as follows: (1) archive management process which includes removing, structuring and storaging, servicing, and destructing have been arranged and well executed; (2) a problem which often occurs is at the stage of structuring the less managed archive that is accepted from Work Unit. It influence the time efficiency in the archival management; (3) some certain activities in archive management is assisted by the third parties which in such matters is K3LH expert team so that the archival activity runs percisely,Â  and; (4) Archival Center organizes a preventive action to keep the archive safety. From the employment side, the company coordinated with several parties and carry out various activities such as training, certification, workshops, technical guidance, as well as an archival competition.Â Keyword: management, in-active records, K3LH, Record Center.